Microstructure evolution of poly[tetrafluoroethylene-co-(perfluoropropylvinylether)] films under uniaxial deformation. (2nd September 2016) - Yin, Chaoqing; Miranda, Daniel F.; Zhang, Shihai; Zhang, Qinghua; Runt, James
Abstract: This paper presents an investigation of semi-crystalline poly[tetrafluoroethylene -co-(perfluoropropylvinylether)] (PFA) films uniaxially drawn at two temperatures. The extent of crystal unit cell orientation increased significantly with drawing at both draw temperatures as expected, but crystallinity was found to increase with draw ratio only at the lower draw temperature, remaining unchanged at the higher temperature. Considering the evolution of small-angle X-ray scattering patterns as a function of deformation, a model for the changes in PFA lamellar microstructure on drawing was developed. The observed mechanical α and γ relaxations of PFA were assigned to relaxation of rigid and mobile amorphous segments, respectively. Drawing at 200 °C to a draw ratio of 7 leads to a ∼40 °C increase in the α transition temperature compared to the unoriented film, and the findings support the key role of molecular orientation in suppressing the cooperative motions of non-crystalline segments in drawn polymers. Graphical abstract: Highlights: Uniaxial drawing of fluoropolymer films imparted significant changes to microstructure and thermophysical properties. Achieved higher crystallinity and very high crystal orientation (fc > 0.9) through drawing. Segmental relaxations were greatly impeded by orientation.